PREVALENCE OF BACTERIAL VAGINITIS AMONG WOMEN USING DIFFERENT TYPES OF IUDS - Marwa Najat Ahmed; Asal Aziz Tawfeeq; Khalidah Mohammed Amin (Journal of Medical Genetics and Clinical Biology, 2024)
Background: A coil, also known as an intrauterine contraceptive device (IUCD or ICD), is a small birth control method that is put into the uterus to stop pregnancy. It usually starts in the endocervix and vagina and spreads up the body, causing endometritis, salpingitis, tubo-ovarian abscesses, parametritis, oophoritis, and/or pelvic peritonitis. objective: The objective of the current study was to investigate the prevalence of bacteria causing vaginitis among women using different types of intra uterine devices Materials and methods: The study was conducted in Kirkuk city from November 1, 2023, to April 30, 2024, using high vaginal swabs from 186 fertile women using intrauterine devices (IUDs). Demographic, medical, and gynecologic histories were recorded, and all patients underwent pelvic examinations. Swabs from the posterior fornix of the vagina were taken for microbiological analysis. The study included women aged 18-45 using IUDs, and excluded those who had received antibiotics, had preexisting systemic or infectious diseases, or experienced bleeding. Ethical approval was obtained, and informed consent was signed by all participants. The swabs were cultured on blood agar , MacConkey agar, Mannitol salt agar and deman rosa sharpe agar and Eosin methylene blue agar and incubated at 37°C for 24 hours. The colonies were picked, purified, and identified through a series of biochemical tests, including Gram staining, motility tests, and enzyme and fermentation tests. The Vitek 2 system was used for microbial identification and susceptibility testing. Results: In a study of 148 women using copper IUDs, 66 (44.59%) tested positive for vaginal swab cultures, while 82 (55.41%) tested negative. Similarly, among 38 women using hormonal IUDs, 17 (44.74%) had positive culture results, and 21 (55.26%) tested negative. Overall, out of 186 women tested, 83 (44.62%) had positive cultures. Among the 83 positive cases, 66 (79.52%) were in copper IUD users, and 17 (20.48%) were in hormonal IUD users. Escherichia coli was the most common bacterium, found in 40.91% of positive cultures, followed by Staphylococcus epidermidis (13.64%), and other bacteria including Staphylococcus aureus, Actinomyces israelii, and Proteus mirabilis, each at 9.09%. In women with positive cultures using copper IUDs, E. coli was most prevalent (47.06%), followed by Staphylococcus aureus and Staphylococcus epidermidis (17.65% each). Among women with positive cultures, 13.25% had diabetes, compared to 4.85% with negative cultures. Hypertension was present in 3.61% of women with positive cultures versus 1.94% with negative cultures. Duration of IUD use also showed a significant correlation with culture results. Women with positive cultures using copper IUDs had the highest percentage in the 1-2 year duration category (43.94%), while those using hormonal IUDs had the highest in the same category (47.06%). Antibiotic sensitivity testing revealed that Imipenem, Meropenem, Tigecycline, and Colistin were 100% effective against E. coli isolates from women using IUDs. However, high resistance rates were observed for Ampicillin/Sulbactam (71.79%) and Ciprofloxacin (84.62%). Ceftolozane/Tazobactam and Gentamicin had relatively high sensitivity rates, while Ceftazidime/Avibactam showed moderate sensitivity. Conclusions The study reveals a significant proportion of women with copper and hormonal IUDs tested positive for vaginal infections, with Escherichia coli being the predominant bacterium isolated,significant differences were noted in the clinical presentation and comorbidities of women with positive cultures compared to those with negative cultures.study identified antibiotics with high sensitivity rates against E. coli isolates, such as Imipenem, Meropenem, Tigecycline, and Colistin, highlighting potential treatment options for IUD-associated infections caused by multidrug-resistant strains. Conversely, antibiotics like Ampicillin/Sulbactam and Ciprofloxacin demonstrated high resistance rates